Atraumatic acute bilateral quadriceps tendon rupture in a patient with bilateral patella spurs. A case report and review of literature - Pagliari, Micaela; Menna, Carlo Raimondo; Migliorini, Andrea; Molinari, Marco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: the spontaneous and simultaneous rupture of both quadriceps tendons is uncommon and has rarely been reported in medical literature. The current case involves a 62-years old man with bilateral atraumatic complete quadriceps tendon rupture. Aim of this study is to provide a systematic review of this case and a literature review of similar cases. Methods: we reviewed and analyzed this patient's records. Initial x rays of both knees showed a bilateral patellar spur. Real time ultrasonography scan of both knees showed a complete tear of quadriceps. The repair has consisted on end to end Krackow sutures associated with bone suture to the proximal pole of the patella using patellar drill holes. We also researched the literature for bilateral simultaneous rupture of the quadriceps tendon. Results: The patient suffered only from seasonal asthma (receiving only inhaled corticosteroids) and he was overweight (BMI: 33,5), he did not do any type of sport, he was a biker. The patient was able to walk after 3 weeks with both knee cast. The patients had a 120° pain free range of motion in both knees 4 months after surgery. Conclusion: Simultaneous bilateral quadriceps tendon rupture is really very rare and these are generally reported as case presentation in the literature. This injury usually presents in middle aged people with a history of chronic illness. The general recommendation is to perform surgical intervention within 48-72 hours after injury.